Empirical contribution of the eco-efficiency of water consumption of companies that were part of a Mexican stock market index (Revista Científica Compendium, 2025)
This research confirms that companies improving their environmental performance also improve their economic performance. This conclusion is drawn from the collection, analysis, and interpretation of data from 2019 to 2024 of listed firms that, in July 2025, were the top 10 components by weighting of the S&P/BMV IPC EGS T Index of the Mexican Stock Exchange. This analysis was conducted by calculating the 'eco-efficiency formula' and obtaining the water consumption eco-efficiency index. The aim is to contribute to the development of an experimental framework for the Theory of Eco-efficiency through a documentary study of the financial and sustainability reports published by these same business organizations.
Keywords: eco-efficiency theory; water consumption; corporate sustainability